Unpacking the sweet deal exploring the stigma of sugar babies. - Fernandez, Kate M. (Kate M. Fernandez, 2018)
This thesis explores the experiences of stigma of male and female sugar babies. In-depth qualitative interviews were conducted with six sugar babies in Tacloban City who are all in long term relationships with their sugar daddies. The results indicated that all sugar babies are motivated to engage in sugar dating due to their lack of financial resources. The transactional nature of sugar dating has been the ground for its likelihood to prostitution. In addition, key findings show that sugar babies' stigma experiences are both classed and gendered. There are sugar babies who are stigmatized for engaging in sugar dating due to poverty. Moreover, the stigma male and female sugar babies experience are disproportionately targeted by the stigma that surrounds sugar dating. This posits that the interaction of the social identities, gender and class, in the stigma sugar babies experience indicate the complexity of this phenomenon.
Undergraduate thesis (B.A. Psychology) -- University of the Philippines, Tacloban.